Economic cooperation as an instrument of confidence-building: The case of Pakistan And India / Hafiz Muhammad Tahir Ashraf - Hafiz Muhammad Tahir , Ashraf (2017)
The nature of the Pakistan–India conflict has been portrayed as an ‘enduring rivalry’ and its essential trait is ‘persistence’. Fundamental to their antagonism is the territorial dispute over Kashmir. Negotiations are occasional, but both nations infrequently make goodwill gestures. Peace initiatives such as the Tashkent Declaration in 1966, the Simla Accord in 1972, the Lahore Declaration in 1999, the Agra Summit in 2001 and the process of the Composite Dialogue in 2004 are amongst the most important peace overtures carried out by Pakistan and India. However, dialogues at the secretary level were stalled after the Mumbai attack in 2008. Moreover, India frequently started accusing Pakistan of sponsoring terrorism in her territory. The Pakistan–India peace process portrays the constant upheaval in this bilateral relationship. If one step has been taken forward, two steps are then taken backward. The foremost reason for this is the prevalence of a trust deficit between Pakistan and India. Normalized relations between Pakistan and India are essential for the progress and development of South Asia. The regional economic grouping of South Asian nations, i.e. SAARC, has been held as a hostage of the Pakistan–India conflict and consequently has not become successful in enhancing regional economic cooperation among member countries mainly due to the persistent antagonism between Pakistan and India. With this backdrop, conflict resolution assumes a new urgency and managing the Pakistan–India conflicts becomes more vital. This study evaluates the adoption of a distinctive approach towards managing the Pakistan–India conflict. By placing bilateral economic cooperation under the umbrella of Confidence Building Measures (CBMs), this study examines the prospects of enhanced economic cooperation between Pakistan and India. Mitrany and Hass’s neofunctionalism has been applied to manage the Pakistan–India conflict. It also analyzes its spillover effect on the politico security relationship between the two nuclear weapon neighbors. Regarding the research methodology used in this study, an inductive approach has been adopted in this study. A qualitative research method has been used in this study. Primary as well as secondary sources have been used to collect data for this study. Primary data was collected through interviews of Key Informants (KIs) and government documents. Secondary data refers generally to research carried out by other people. This study mainly focuses on the interviews of the KIs. A questionnaire was used for the in-depth interviews (IDIs) with businessmen, representatives of chambers of commerce and industries, academicians, researchers, analysts and journalists from Pakistan and India in this study. To enhance economic cooperation between Pakistan and India, this study identifies the removal of physical barriers, such as a lack of modern facilities at trade crossings between Pakistan and India, inept infrastructure and the removal of non-tariff barriers (NTBs). Also, this research emphasizes that additional trade arteries should be opened up between Pakistan and India such as the Bahawalnagar–Fazilka, the Khokhrapar–Munabao, the Sialkot–Jammu and trade openings at the line of control (LoC) in the disputed territory of Jammu and Kashmir. The study also finds significant potential for joint ventures between Pakistan and India for win-win approaches in trade and economic links. This study considers the current governments, which are pro-business, as catalysts to the launching of economic cooperation and these governments can create conducive environment for initiating peace overtures to manage the conflictual relationship of Pakistan and India.